(untitled) - Quinlan, Joseph P. (Berkeley, Calif., 1995)
Contents: Ten things business should know about Vietnam; The political landscape; Vietnam an economic overview....
Keywords: Đầu tư, nước ngoài,Investments, Foreign; Việt Nam,Vietnam